Upgrading argan shell wastes in wood plastic composites with biobased polyethylene matrix and different compatibilizers - Jorda Reolid, Maria (2021)
The present study reports on the development of wood plastic composites (WPC) based on micronized argan shell (MAS) as a filler and high-density polyethylene obtained from sugarcane (Bio-HDPE), following the principles proposed by the circular economy in which the aim is to achieve zero waste by the introduction of residues of argan as a filler. The blends were prepared by extrusion and injection molding processes. In order to improve compatibility between the argan particles and the green polyolefin, different compatibilizers and additional filler were used, namely polyethylene grafted maleic anhydride (PE-g-MA 3 wt.-%), maleinized linseed oil (MLO 7.5 phr), halloysite nanotubes (HNTs 7.5 phr), and a combination of MLO and HNTs (3.75 phr each). The mechanical, morphological, thermal, thermomechanical, colorimetric, and wettability properties of each blend were analyzed. The results show that MAS acts as a reinforcing filler, increasing the stiffness of the Bio-HDPE, and that HNTs further increases this reinforcing effect. MLO and PE-g-MA, altogether with HNTs, improve the compatibility between MAS and Bio-HDPE, particularly due to bonds formed between oxygen-based groups present in each compound. Thermal stability was also improved provided by the addition of MAS and HNTs. All in all, reddish-like brown wood plastic composites with improved stiffness, good thermal stability, enhanced compatibility, and good wettability properties were obtained.